2007
DOI: 10.1016/j.bbalip.2007.02.013
|View full text |Cite
|
Sign up to set email alerts
|

PPARs and molecular mechanisms of transrepression

Abstract: In the last few years, PPARs have emerged as key regulators of inflammatory and immune responses. However, the mechanistic basis of the anti-inflammatory effects of Peroxisome Proliferator-activated receptors (PPARs) remains poorly understood. Accumulating evidence suggests that these effects result from inhibition of signal-dependent transcription factors that mediate inflammatory programs of gene activation. Several mechanisms underlying negative regulation of gene expression by PPARs have been described. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
445
1
13

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 489 publications
(467 citation statements)
references
References 113 publications
8
445
1
13
Order By: Relevance
“…Kennedy et al (2008) recently reported that trans-10, cis-12 CLA antagonized ligand activation of PPARg in adipocyte cell culture, presumably via extra cellular signalregulated kinases (ERK), specifically ERK-stimulated phosphorylation of PPARg. Ligand-dependent and -independent repressor mechanisms are well described for the PPARs, but they function primarily to reduce inflammatory and immune responses (Ricote and Glass, 2007); indeed a hematopoietic and endothelial cell-specific PPARg knock-out resulted in increased levels of inflammatory molecules in milk (Wan et al, 2007). Lastly, CLA treatment reduced body fat in PPARa knock-out mice, demonstrating a PPARa-independent mechanism for CLA in growing mice (Peters et al, 2001).…”
Section: Sterol Response Element-binding Protein-1mentioning
confidence: 98%
“…Kennedy et al (2008) recently reported that trans-10, cis-12 CLA antagonized ligand activation of PPARg in adipocyte cell culture, presumably via extra cellular signalregulated kinases (ERK), specifically ERK-stimulated phosphorylation of PPARg. Ligand-dependent and -independent repressor mechanisms are well described for the PPARs, but they function primarily to reduce inflammatory and immune responses (Ricote and Glass, 2007); indeed a hematopoietic and endothelial cell-specific PPARg knock-out resulted in increased levels of inflammatory molecules in milk (Wan et al, 2007). Lastly, CLA treatment reduced body fat in PPARa knock-out mice, demonstrating a PPARa-independent mechanism for CLA in growing mice (Peters et al, 2001).…”
Section: Sterol Response Element-binding Protein-1mentioning
confidence: 98%
“…The ability of PPARs to regulate gene transcription is complex, utilizing ligand-dependent transactivation or ligand-independent target gene repression (reviewed in 37 ). In classic ligand-dependent transactivation, ligand binding induces a conformational change in protein structure that stabilizes heterodimerization with the 9-cis retinoic acid receptor (RXR).…”
Section: Peroxisome Proliferator-activated Receptors (Ppar)mentioning
confidence: 99%
“…PPARs can also influence the expression of genes lacking a PPRE. In this case, PPARs act through ligand-dependent transrepression to inhibit the functions of other transcription factors, most notably nuclear factor -kB (NF-kB) and activator protein-1 (AP-1) 37 . This occurs through multiple mechanisms, including direct interaction of PPAR with the transcription factor, competition for co-activator recruitment, and regulation of mitogen-activated protein kinase (MAPK) family member activity 37 .…”
Section: Peroxisome Proliferator-activated Receptors (Ppar)mentioning
confidence: 99%
See 2 more Smart Citations